Measuring effects of second wave activation: A theoretical model and tutorial for activation programme evaluation - Rickard Ulmestig; Ingeborg Waernbaum (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
This article develops a theoretical model for evaluating mandatory activation of welfare recipients in complex activation programmes. The model aims to summarize and describe heterogeneous content that is difficult to comprehend because of local variations, staff characteristics, or other reasons that can blur the descriptions of the programme. Furthermore, the content can be difficult to describe due to a weak correspondence between the official rhetoric concerning a programme and what researchers discover when observing it. We use a two-dimensional variable in our study that is intended to identify essential characteristics for capturing generic components of activation programmes. We use experience from an on-site interview study and on-site observations about 18 programmes to demonstrate how the proposed model can be used to evaluate the effect of the programmes. We evaluate the effects of programme participation on income in this study while adjusting for pre-treatment confounding variables, to test the model.
Keywords: Z18; C14; 330; Activation; Active labour market policy; Causal inference; Programme evaluation; Unemployment; Work-first approach